Glymphatic system dysfunction in temporal lobe epilepsy patients with hippocampal sclerosis. Issue 2 (27th March 2022) - Lee, Dong Ah; Park, Bong Soo; Ko, Junghae; Park, Si Hyung; Lee, Yoo Jin; Kim, Il Hwan; Park, Jin Han; Park, Kang Min
Abstract: Objective: This study aimed to evaluate glymphatic system function in temporal lobe epilepsy (TLE) patients with hippocampal sclerosis (HS) in comparison to healthy controls, using diffusion tensor imaging (DTI)‐analysis along the perivascular space (ALPS) method. We hypothesized that there is glymphatic system dysfunction in TLE patients with HS. Methods: We retrospectively enrolled 25 TLE patients with HS and 26 age‐ and sex‐matched healthy controls. All participants underwent DTI with the same 3T magnetic resonance imaging scanner, and the DTI‐ALPS index was calculated. We evaluated the differences in the DTI‐ALPS index between TLE patients with HS and healthy controls. Moreover, we evaluated the correlation between the DTI‐ALPS index and clinical characteristics of epilepsy, including age, age at seizure onset, duration of epilepsy, and number of anti‐seizure medications (ASMs). Results: There was a difference in the DTI‐ALPS index between TLE patients with HS and healthy controls. The DTI‐ALPS index in TLE patients with HS was lower than that in healthy controls (1.497 vs. 1.668, P = .015). However, there was no difference in the DTI‐ALPS index between the newly diagnosed TLE patients with HS and the chronic TLE patients with HS. The DTI‐ALPS index was negatively correlated with age ( r = −0.420, P = .036). However, the DTI‐ALPS index was not correlated with other clinical characteristics, including age at seizure onset, duration of epilepsy, and number of ASMs. Significance: Our findings showed that the DTI‐ALPS index was significantly lower in TLE patients with HS than in healthy controls, indicating the presence of glymphatic system dysfunction in TLE patients with HS. Our study also suggests that the DTI‐ALPS method may be useful for evaluating glymphatic system function in epilepsy.